Eswatini. Maßnahmen zur Verbesserung der Kulturgüterschutzinfrastruktur. Die Arbeiten der Jahre 2017 und 2018 - Linstädter, Jörg (e-Forschungsberichte des DAI, 2019)
The DAI is currently engaged in several activities in Eswatini (former Swaziland). In 2017, we supplied the National Museum with shelves and packaging material and during two campaigns repacked all artefacts from the old excavations. These were then brought to a new store room, relabeled and reorganized and made assessable for future research. Furthermore, we are supporting the Eswatini National Trust Commission set up a national heritage register by relocating old sites and conducting surveys to discover new sites. In 2019, we will document the endangered site Enkambeni. Finally, we are supporting the University of Eswatini (UNESWA), initiate an archaeology study program. After offering a field school in 2017, we designed an introductory module which is currently being proposed to the university senate.